2006
DOI: 10.1093/jb/mvj135
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional Characterization of Herpes Simplex Virus 1 Immediate-Early Protein Infected-Cell Protein 22

Abstract: Of the five HSV1 immediate-early proteins, infected-cell protein 22 (ICP22), the product of the Us1 gene, is a member whose function is less understood. In order to promote better understanding of the role of ICP22 in viral replication, mutation and fluorescence techniques were used to investigate the biochemical relationship between ICP22's structure and nuclear localization, and the CAT assay was used to analyze the relationship between ICP22's structure and its transcriptional repression. The results of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 25 publications
3
19
0
Order By: Relevance
“…1C, panel a) localized diffusely in the nucleus and to discrete nuclear bodies. This pattern is similar to that which has been reported by others for transiently expressed ICP22 (7,48,54). In contrast, the US1.5 form of the protein (Fig.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…1C, panel a) localized diffusely in the nucleus and to discrete nuclear bodies. This pattern is similar to that which has been reported by others for transiently expressed ICP22 (7,48,54). In contrast, the US1.5 form of the protein (Fig.…”
Section: Resultssupporting
confidence: 91%
“…The nature of the ICP22-containing nuclear bodies is currently unknown, although their presence in transfected cells indicates that they are either preexisting cellular structures or are induced de novo by ICP22. Recent work indicates that they do not correspond to PML domains, Cajal bodies, or SC35-containing nuclear speckles (7,48), although they appear to have a paired spatial relationship with SC35 speckles (7,48). Whatever their physical nature, our results demonstrate two important points concerning their relationship to ICP22.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…This study further demonstrated that the repressive function of ICP22 was partially abrogated by coexpression of the U L 13 gene, which encodes a viral Ser/Thr kinase. The observed repression of viral gene expression by ICP22 first noted by Prod'hon et al has been corroborated by several groups (2,5). To date, however, the mechanism underlying this repression remains unclear.…”
Section: Replication Of Icp22mentioning
confidence: 66%
“…Using the pCDNA3:ICP22 expression cassette, Fraser and Rice demonstrated that ICP22 alone is sufficient to alter the phosphorylation state of the C-terminal domain of RNA Pol II. A similar strategy using the pCDNA3 vector was employed by Cun et al to demonstrate transcriptional repression by ICP22 alone (2). The use of the CMV promoter in pCDNA3 as an engine to drive ICP22 expression presents numerous opportunities for screening and characterizing mutant forms of ICP22 without the need to introduce mutations directly into the viral genome.…”
Section: Replication Of Icp22mentioning
confidence: 99%